Minat beli produk halal bukan lagi menjadi Prioritas namun sebuah Keharusan - Budhiawan, Muhhamad Arif; Mangifera, Liana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Globalization encourages consumers to be more selective in purchasing a product. For Muslims, of course they really pay attention to the halal label on every product they choose. The halal concept is not only of interest to Muslims, but also the general public can get products that are certified halal. This research used data from 153 students at Islamic universities in Surakarta, including Muhammadiyah University of Surakarta, Batik Islamic University of Surakarta, and UIN Raden Mas Said Surakarta. This research uses consumer behavior theory with multiple linear analysis methods. This research focuses more on consumer interest in buying halal goods. Previous research regarding halal products is still quite small. This research also adds a priority scale as a mediator, which in previous studies did not use a priority scale as a mediator. This research aims to explain the relationship between brand image, company image and product quality variables with interest in purchasing halal goods. This research states that the priority scale cannot be an effective mediator. Interest in purchasing halal products is not a priority for students at Islamic universities in Surakarta, but has become a necessity or obligation that should be carried out.